The Impact of Customer Relationship Management Quality and Company Reputation toward the Antecedent of Customer Loyalty during COVID-19 Pandemic - Gunawan, Victor; Astuti, Rifelly Dewi; Bustaman, Yosman (ADI Publisher, 2021)
This study objective was found the interrelationships among service evaluation, that is service quality, customer satisfaction, and customer value, with customer loyalty through mediating roles of customer relationship management (CRM) quality, and moderating roles of company reputation in the heavy equipment industry in the middle of COVID-19 pandemic. Also investigate the most critical domains of service quality, customer satisfaction and customer value considered by customers in the heavy equipment and the connection among service quality, customer value and customer satisfaction toward customer loyalty by interlinking customer relationship management (CRM) quality and moderating effect of company reputation variable. In this research, there are several variables correlated with customer loyalty, CRM Quality and Company Reputation. Data were gathered from 259 customer, had transaction unit heavy equipment and its product support in the time of COVID-19 pandemic, by using SPSS and SmartPLS. The data is processed and analyze through structural equation model (SEM). The research found service quality and customer satisfaction variables were not influenced customer loyalty and the mediating effect of CRM quality on relationship between service quality toward customer loyalty were not supported too. Although, customer satisfaction has strong correlation to customer loyalty and the mediating effect is supported in the middle of COVID-19 pandemic. In addition, this research also found moderating effect of company reputation is significance on relationship service quality, customer value, and customer satisfaction toward CRM quality, even if the correlation is reverse relationship. The research discusses important implications considering the effect of service quality, customer satisfaction and mediated by CRM quality toward customer loyalty and improving company reputation as moderated effect to strengthen customer relationship management quality.